How medical students learn ethics: an online log of their learning experiences. Issue 10 (15th July 2015) - Johnston, Carolyn; Mok, Jonathan
Abstract : Medical students experience ethics learning in a wide variety of formats, delivered not just through the taught curriculum. An audit of ethics learning was carried out at a medical school through a secure website over one academic year to determine the quantity and range of medical ethics learning in the undergraduate curriculum and compare this with topics for teaching described by the Institute of Medical Ethics (IME) (2010) and the General Medical Council's (GMC) Tomorrow's Doctors (2009). The online audit captured the participants' reflections on their learning experiences and the impact on their future practice. Results illustrate the opportunistic nature of ethics learning, especially in the clinical years, and highlight the reality of the hidden curriculum for medical students. Overall, the ethics learning was a helpful and positive experience for the participants and fulfils the GMC and IME curriculum requirements.